2021
DOI: 10.3892/or.2021.8100
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibition and microRNA‑199a‑5p upregulation in paclitaxel‑resistant A549/T lung cancer cells

Abstract: Multidrug resistance (MDR) is one of the major reasons for the clinical failure of cancer chemotherapy. Autophagy activation serves a crucial role in MDR. However, the specific molecular mechanism linking autophagy with MDR remains unknown. The results of the present study demonstrated that autophagy was inhibited and microRNA (miR)-199a-5p levels were upregulated in MDR model lung cancer cells (A549/T and H1299/T) compared with those in the parental cell lines. Paclitaxel (PTX) treatment increased the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In conclusion, the miR-199a-5p/p62 axis regulates autophagy as a potential mechanism of cisplatin resistance in SCLC [ 43 ]. Zeng et al [ 79 ] showed that miR-199a-5p expression was up-regulated in paclitaxel-resistant lung cancer cell lines (A549 and H1299). The low expression of miR-199a-5p induced autophagy and made cells re-sensitive to chemotherapy drugs, while the overexpression of miR-199a-5p inhibited autophagy and desensitized cells to various chemotherapy drugs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the miR-199a-5p/p62 axis regulates autophagy as a potential mechanism of cisplatin resistance in SCLC [ 43 ]. Zeng et al [ 79 ] showed that miR-199a-5p expression was up-regulated in paclitaxel-resistant lung cancer cell lines (A549 and H1299). The low expression of miR-199a-5p induced autophagy and made cells re-sensitive to chemotherapy drugs, while the overexpression of miR-199a-5p inhibited autophagy and desensitized cells to various chemotherapy drugs.…”
Section: Resultsmentioning
confidence: 99%
“…After all, its expression is high in some lung cancer drug-resistant cell lines. Additionally, and this is a puzzling point, miR-199a expression is up-regulated in paclitaxel-resistant lung cancer cell lines [ 79 ] and down-regulated in doxorubicin-resistant lung cancer cell lines [ 80 ]. This may be because the two different drug treatments resulted in different biological responses and the activation of signaling pathways in the lung cancer cell lines, leading to different downstream targets of miR-199a regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, early diagnosis and treatment of tumors have long been a hot topic in medicine and life sciences [42][43][44]. Zeng et al reported that upregulation miR-199a-5p inhibits autophagy and renders resistance to chemotherapeutic drugs in lung cancer cells by activating the PI3K/Akt/mTOR pathway and targeting p62 [45]. We will also continue to monitor the impact of the miR-199a/Rheb/mTOR axis on the development of resistance to the treatment of tumors in lung cancer, especially about EGFR-TKIs resistance.…”
Section: Discussionmentioning
confidence: 99%
“…miR-342 has also been demonstrated to act as a tumor suppressor gene that inhibits the growth of colorectal carcinoma by regulating aberrant DNA hypermethylation [38]. Currently, miR-199a-5p is primarily being investigated in cancers, including epithelial ovarian cancer and lung cancer [39,40]. Pathways linked to miR-199a-5p have also been implicated in the inflammatory response to certain diseases.…”
Section: Discussionmentioning
confidence: 99%